Estimating inorganic arsenic exposure from rice intake in Chinese Urban Population. (August 2020) - Zhou, Zheng; Kang, Yijin; Li, Huanhong; Cao, Suzhen; Xu, Jianhua; Duan, Xiaoli; Yang, Guiling; Shao, Kan
Abstract: Background: Rice intake is a major route of oral exposure to inorganic arsenic (iAs), a known human carcinogen. The recent risk assessment on iAs in rice conducted by the US Food & Drug Administration (FDA) didn't propose an action level for iAs in rice mainly because of the relatively low consumption rate in the general US population. However, this decision may not be applicable to high rice-intake populations, such as the Chinese population. Objective: The objective of this study was to probabilistically characterize the exposure of iAs via rice intake in Chinese population with a focus on the urban population. Methods: With the consideration of bioaccessibility of iAs in rice, iAs exposure is mainly determined by rice intake rate and iAs concentration in rice. To estimate the daily rice consumption, a dietary survey consisting of 1873 subjects was conducted in three major Chinese cities (Beijing, Guangzhou, and Hangzhou). Speciated As concentration in rice was measured using 480 rice samples collected from markets in these three cities. Monte Carlo simulation approach was applied to distributionally estimate the average daily dose (ADD) of iAs through rice intake. Results: The estimated distribution of daily iAs exposure of the study population has a mean of 10.5 μg/day with a 95th percentile interval from 0.1 to 75.3 μg/day. The estimated distribution of ADD has a mean of 0.179 μg/kg/day with a 95th percentile interval from 0.001 to 1.224 μg/kg/day. Greater level of iAs exposure (due to higher rice intake) was observed in males than females, and in summer than other seasons with lower temperature. Geographically, the ADD of iAs exposure from rice intake reduces from south to north. Conclusions: About 13% of the Chinese urban population are exposed to iAs via rice intake higher than the Reference Dose (RfD) level. Graphical abstract: Image 1 Highlights: Rice intake is a major dietary route of exposure to inorganic arsenic (iAs). Data were collected on rice intake and concentration of iAs in rice. Monte Carlo simulation is used for probabilistic estimation of distribution of iAs exposure. Increased daily rice intake contributes to elevated exposure of iAs. 13% of study population having average daily dose exceeding U.S. EPA reference dose.